Compounds for selective translational inhibition. (August 2022) - Shichino, Yuichi; Iwasaki, Shintaro
Abstract: Since many human diseases are caused by the unwelcome production of harmful proteins, compounds that selectively suppress protein synthesis should provide a unique path for drug development, expanding the druggable proteome. Although surveying the RNA/amino acid contexts that are preferentially affected by translation inhibitors has presented an analytic hurdle, the application of a technique termed ribosome profiling overcomes this problem. Indeed, this technique uncovers the selectivity of translation repression by small molecules such as chloramphenicol, macrolides, PF846, and rocaglates. The molecular understanding of how the compounds inspire context selectivity, despite their targeting to general translation machinery, facilitates rational drug design and discovery for therapeutic purposes. Highlights: Context-specific translation inhibitors allow the targeting of undruggable proteins. Ribosome profiling is the gold standard for surveying compound selectivity in translation. Macrolides and PF846 halt ribosome traverse in a specific amino acid context. Rocaglates repress translation initiation in an RNA sequence-selective manner.